Antibiotics Attenuate Methamphetamine-Induced Hepatotoxicity by Regulating Oxidative Stress and TLR4/MyD88/Traf6 Axis - Chen, Li-Jian; He, Jie-Tao; Pan, Ming; Liu, Jia-Li; Zhang, Kai-Kai; Li, Jia-Hao; Wang, Li-Bin; Xu, Ling-Ling; Chen, Yu-Kui; Zhang, Qin-Yao; Li, Dong-Ri; Xu, Jing-Tao; et al. (Frontiers in Pharmacology, 2021)
Methamphetamine (METH) is a major psychostimulant drug of abuse worldwide, and its neurotoxicity has been studied extensively. In addition to neurotoxicity, METH can also induce hepatotoxicity. The underlying mechanism of intestinal microorganisms in METH-induced hepatotoxicity remains unclear. In this study, mice have received antibiotics intragastrically or PBS once each day for 1 week, followed by METH or saline. The antibiotics attenuated METH-induced hepatotoxicity as evidenced by histopathological observation and biochemical analysis; furthermore, they alleviated METH-induced oxidative stress. The effect of antibiotics on METH-induced hepatotoxicity was investigated using RNA-sequencing (RNA-seq). The RNA-seq results demonstrated that antibiotics could regulate 580 differentially expressed genes (DEGs), of which 319 were upregulated after METH treatment and then downregulated with antibiotic pretreatment, 237 were first downregulated after METH administration and then upregulated after antibiotic pretreatment, in addition to 11 were upregulated, and 13 were downregulated simultaneously in METH and antibiotic-pretreated groups. RNA-seq analyses revealed that TLR4 is one of the hub genes. Western blot analysis indicated that antibiotics inhibited the increase of TLR4, MyD88, and Traf6 induced by METH. This research suggests that antibiotics may play an important role in preventing METH-induced liver injury by regulating oxidative stress and TLR4/MyD88/Traf6 axis. The elimination of microbiota by antibiotic suggested that gut flora may protect antibiotic preconditioning on METH-mediated hepatotoxicity, though further investigation is required.